2019
DOI: 10.1101/697805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limited recognition ofMycobacterium tuberculosis-infected macrophages by polyclonal CD4 and CD8 T cells from the lungs of infected mice

Abstract: 20Immune responses following Mycobacterium tuberculosis (Mtb) infection or vaccination 21 are frequently assessed by measuring T cell recognition of crude Mtb antigens, 22 recombinant proteins, or peptide epitopes. We previously showed that not all Mtb-23 specific T cells recognize Mtb-infected macrophages. Thus, an important question is 24 what proportion of T cells elicited by Mtb infection recognize Mtb-infected macrophages. 25We answer this question by developing a modified elispot assay using viable Mtb-2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…We use our multi-scale model to determine the proportion of Mtb-specific T cells within granulomas over the course of infection as compared to non-specific T cells present by comparing which frequencies match the dataset derived from NHP. To do this, we varied the frequency of Mtb-specific T cell classes from 1%-25% to capture a potential larger range occurring within primates ( 70 ). For each day of virtual infection, we used GranSim to calculate median, numbers, and proportions of Mtb-specific T cells versus non-specific T cells found within simulated granulomas ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use our multi-scale model to determine the proportion of Mtb-specific T cells within granulomas over the course of infection as compared to non-specific T cells present by comparing which frequencies match the dataset derived from NHP. To do this, we varied the frequency of Mtb-specific T cell classes from 1%-25% to capture a potential larger range occurring within primates ( 70 ). For each day of virtual infection, we used GranSim to calculate median, numbers, and proportions of Mtb-specific T cells versus non-specific T cells found within simulated granulomas ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that T cells localize to and are rapidly recruited into mycobacterial granulomas in the absence of antigen recognition ( 36 38 ). One study found around 5-20% of CD4+ T cells recognize Mtb-infected macrophages by 19- to 22-weeks post infection ( 70 ). Comparatively in GranSim , 10%–20% T cells are Mtb-specific T cells 7- to 28-weeks post infection, with only Mtb-specific T cells given activation capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the selection of epitopes fixes with MHC is an essential aspect in predicting potent T-cell epitopes 75 . Also, CD4 + and CD8 + T-cells' recognition is critical while developing multi-epitope-based vaccines 76 , 77 . We predicted B and T-cell epitopes from the nominated antigens and joined them using AAY and GPGPG linkers in order to construct epitope-based vaccine 78 .…”
Section: Discussionmentioning
confidence: 99%
“…36 This original pool, named "MTB300", and versions thereof have been used by a number of studies to measure and phenotype Mtb-specific responses. 28,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] Due to the overlap of epitopes recognized by different species MHC this pool has also been shown to capture T cell reactivity in mice and nonhuman primates. 38,41,44,49,50 These studies have contributed to our understanding of immunity against Mtb and other mycobacteria.…”
Section: Epitope Meg Ap Ool S a S A Univer Sal Tool For Me A Suring CD 4 T Cell Re S P On S E Smentioning
confidence: 99%